Contralateral eye comparison of the phacoemulsification metrics, patient experience and clinical outcomes in patients undergoing bilateral cataract surgery with two commonly used femtosecond laser systems - Khodabakhsh AJ (Dove Medical Press, 2018)
Afshin James Khodabakhsh, John Hofbauer Beverly Hills Institute of Ophthalmology, Beverly Hills, CA, USA Purpose: The purpose of the study was to compare phacometrics, patient experience factors and clinical outcomes in patients undergoing bilateral laser-assisted cataract surgery using two common femtosecond laser platforms. Setting: This study was conducted in Beverly Hills Institute of Ophthalmology, Beverly Hills, California, USA. Study design: This was a prospective, comparative, contralateral eye study. Methods: Femtosecond laser-assisted cataract surgery was performed in the first eye of 50 patients with bilateral cataract (mean age 69.9 ± 8.61 years) using either the Catalys (Johnson & Johnson Vision) or the LenSx (Alcon Laboratories, Inc.) laser system. The fellow eye was treated with the laser not used in the first eye. The primary outcome measures included overall procedural times, and the secondary outcome measures included patient experience with the two laser systems. Results: There were no statistical differences between the two groups in terms of patient interface preparation time and number of docking attempts as well as effective phaco time, average phaco power, total ultrasound time and nucleus removal time. However, the LenSx group demonstrated a significantly longer cortex removal time and higher perception of pressure and vision loss (p < 0.001) compared to the Catalys group. A significantly higher number of Catalys eyes achieved complete capsulotomy (p < 0.001). The ease of cortex removal was also better in the Catalys group. Postoperative visual acuity, keratometry, endothelial cell count and intraocular pressure were comparable in the two groups. Conclusion: With similar phacometric and clinical outcomes, both laser platforms were efficient, safe and effective during cataract surgery; however, the Catalys group demonstrated superior outcomes in terms of the patient experience, completeness of capsulotomy and ease of cortex removal. Keywords: femtosecond laser-assisted cataract surgery, Catalys, liquid optics interface, LenSx, curved contact lens, subconjunctival hemorrhage